Abordagens e enfrentamento da morte de pacientes idosos : percepções de um grupo de médicos - Poletto, Sadi (2012)
Because of the advance in health technology, medicine professionals have been trying to increase people´s life expectancy in many different ways, postponing death using many times artificial means. The aim of the present study is to get knowledge of experience and approach of doctors related to the process of death and dying of the elderly in hospital environment. For that purpose, a data collecting was made through a semi-structured interview held between April and September 2011. Eleven doctors who work in a well known hospital in the country of Rio Grande do Sul took part on it. Through the analysis of the collected data, it was possible to build some categories: the elderly death experience in medicine practice, doctors and their peers perception, confrontation with those who experienced nearing life ending, management of behaviors and talks about academic formation. The study revealed the medicine professional s concerning on taking care of the patient and the respect to the family, but enhancing the need to careful consideration through deep and large debate about academic formation in order to provide subsidies for behavior management and confrontation strategies related to the treatment of the elderly close to life ending. This way, the study made it possible to prove that more value is given to human beings life in the relationship doctor-patient in the process of death and dying of the elderly in the hospital environment respecting their autonomy and dignity. From the results achieved it can be concluded that the management behavior has its eyes directed to the respect to Medicine bioethical principles and the Code of Ethics